2016
DOI: 10.3390/ma9090740
|View full text |Cite
|
Sign up to set email alerts
|

Protein/Peptide Aggregation and Amyloidosis on Biointerfaces

Abstract: Recently, studies of protein/peptide aggregation, particularly the amyloidosis, have attracted considerable attention in discussions of the pathological mechanisms of most neurodegenerative diseases. The protein/peptide aggregation processes often occur at the membrane–cytochylema interface in vivo and behave differently from those occurring in bulk solution, which raises great interest to investigate how the interfacial properties of artificial biomaterials impact on protein aggregation. From the perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 127 publications
0
13
0
Order By: Relevance
“…Polystyrene is a hydrophobic polymer known to interact with hydrophobic patches on solutes, such as those presented by unfolded proteins (Thormann et al, 2008;Faghihnejad and Zeng, 2012;Shen et al, 2012;Lu et al, 2016). By contrast, surfaces coated with polyethylene glycol present a non-ionic hydrophilic environment that mitigates protein adsorption and concomitant unfolding (Alcantar et al, 2000;Shen et al, 2012;Lu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polystyrene is a hydrophobic polymer known to interact with hydrophobic patches on solutes, such as those presented by unfolded proteins (Thormann et al, 2008;Faghihnejad and Zeng, 2012;Shen et al, 2012;Lu et al, 2016). By contrast, surfaces coated with polyethylene glycol present a non-ionic hydrophilic environment that mitigates protein adsorption and concomitant unfolding (Alcantar et al, 2000;Shen et al, 2012;Lu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between amyloidogenic proteins and membrane surfaces play a prominent role in fibril formation and toxicity in vivo (Stefani, 2007;Aisenbrey et al, 2008;Lu et al, 2016). Association of proteins onto a surface can increase the effective concentration and reduce the stability of the native state, thereby nucleating aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation process of proteins or peptides can be triggered by hydrophobic-hydrophilic interfaces [68]. Protein-protein interactions in the aggregation process can be electrostatic or hydrophobic.…”
Section: Spatial Organization Of Solvent Molecules Around the Proteinmentioning
confidence: 99%
“…More and more evidences have indicated that the multiscale biological membranes in vivo provide a larger number of reactive sites to interact with dissociative protein/peptides [8,9,10,11], which play a key procedure for their accumulation and fibrillation at very low concentrations [12,13,14]. Various models with different physicochemical properties (e.g., composition [15,16], surface charge [17], hydrophilicity [18], hydrophobicity [19,20], chirality [21,22,23,24] and size [25,26]) of interfaces have been built to simulate the interaction between peptides and membranes [27]. Some of our previous works [21,28] have verified the chiral effect on Aβ peptides fibrillation and assembly on flat solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%